IMPLEMENTASI PENDIDIKAN MULTIKULTURAL MELALUI RASA TOLERANSI BERAGAMA DI SEKOLAH DASAR NEGERI 1 CIKAMPEK SELATAN JAKARTA - Yayah Maemunah; Astuti Darmiyanti; Ferianto . (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2023)
The rise of SARA conflicts that occur in Indonesia is currently a concern for education in Indonesia. The weak concept of cultural, racial and religious diversity is the cause of conflict in Indonesia. One way that can be done to prevent conflict in Indonesia due to existing diversity is by way of multicultural education in schools and instilling a character of tolerance. The character value of tolerance is an attitude and action that respects differences in religion, ethnicity, ethnicity, opinions, attitudes and actions of other people who are different from themselves. In addition to cultivating the character of tolerance, efforts that can be made by teachers in preventing conflicts are multicultural education. Multicultural education is education that respects, recognizes, assesses, knows, respects and tolerates diversity. Multicultural education and instilling the character of tolerance can be used as a strategic way to develop a sense of tolerance for diversity. The purpose of this article is to describe the cultivation of the character of tolerance and multicultural education in schools in dealing with cultural, racial, religious and linguistic diversity. The implication of this research is that multicultural education can create religious harmony in the midst of a pluralistic society which can then give birth to a civilization and religious harmony, so that people can carry out their worship safely and comfortably according to their respective beliefs.